Reproducibility of patellofemoral CT scan measurements - Delgado-Martínez, A. D. (Springer-Verlag, 2000)
At least seven parameters have been described for the measurement of patellofemoralmalalignment on CT scanning; three of which measure lateral patellar tilt, two lateral patellar shift and two femoral trochlear dysplasia. We studied 22 knees in 18 patients complaining of patellofemoral pain in order to investigate the reproducibility of these methods. CT scans of the patellofemoral joint were performed in each knee at 0° and 20° of flexion. The seven parameters were recorded from each scan by three independent observers in a blind study. The reproducibility was studied by means of the intraclass correlation coefficient (ICC). Parameters measuring lateral patellar tiltshowed excellent reliability (ICC>75%). The measurements of lateral patellar shift and femoral trochlear dysplasia showed a fair or poor correlation (ICC<75%). We suggest that parameters for measuring lateral patellar tilt only should be used from CT scanning when planning treatment for patello-femoral malalignment.